Nursing management and leadership - Roussel, Linda ;Swansburg , Richard J. ;Swansburg, Russell C. (Sudbury, Massachusetts : Jone and Bartlett Learning, 2006)
"The field of health care is increasingly affected by management changes such as organizational downsizing and restructuring, a rise in the temporary workforce, pay-for-performance, and the implementation of total quality management programs, Management and Leadership for Nurse Administrators, Fourth Edition will keep nurses and nursing students abreast of these changes - an essential aspect of their career development." "Organized around the four key management functions of Planning, Organization, Leadership, and Evaluation, the revised text includes new chapters on total quality management, the theory of human resource development, and collective bargaining. Additionally, new content includes recommendations from the Institute of Medicine (Crossing the Quality Chasm, Educating Healthcare Professionals) as well as content on the Magnet Appraisal process and ethics for the nursing manager." "Designed to provide a substantial management and administrative foundation for nurse managers, Management and Leadership for Nurse Administrators, Fourth Edition explore the appropriate concepts, theories, and practical knowledge that will enable them to succeed and excel in today's changing healthcare environment."--BOOK JACKET.
Conceptualization of nursing administration: theory and concepts -- Emotionally-intelligent leadership in nursing and health care organizations -- Ethical principles for the nurse administrator -- The components of change: creativity and innovation, critical thinking and planned change -- Decision-making and problem-solving: communication practices and skills -- Organizational structure and analysis -- Leadership and evidence-based management -- Human resource development: managing a culturally diverse workforce -- The planning process -- Staffing and scheduling -- Principles of budgeting -- The directing process -- eNursing -- Health policy, legal and regulatory issues -- Collective bargaining -- Evaluation -- Quality management -- Performance appraisal -- The nurse manager of staff development.
Includes bibliographical references and index.
Keywords: NURSING SERVICES -- ADMINISTRATION